Exposure to and opinions towards sex education among adolescent students in Mumbai: A cross-sectional survey - Benzaken Tami; Palep Ashutosh H; Gill Paramjit S (BMC, 2011)
Abstract Background The aim of this study was to determine students' exposure to sex education and identify students' perceptions of accessibility to sexual health advice and their preferences in implementing sex education. Methods A cross-sectional study was carried out in junior colleges in Mumbai in 2010. The self-administered questionnaire investigated male and female students' (aged 15-17) exposure and opinions towards sex education. Data was entered into and analysed using SPSS version 17.0. Results The questionnaire was completed by 427 students. Almost 90% of students believed it important to have sex education as part of school curriculum; over 60% reported prior exposure to sex education in school. However, only 45% were satisfied they had good access to advice about contraception and sexual health, particularly, females reported more limited access. Conclusions The majority responding indicated a desire for more widespread implementation of school-based sex education, particularly amongst female respondents.